Mobile web development : building mobile websites, SMS and MMS messaging, mobile payments, and automated voice call systems with XHTML MP, WCSS, and mobile AJAX /: building mobile websites, SMS and MMS messaging, mobile payments, and automated voice call systems with XHTML MP, WCSS, and mobile AJAX. (2008) - Unknown
No abstract available